PAUL DELSALLE, A History of Archival Practice - Stoykovich, Eric C. (Archivaria, 2018)
A History of Archival Practice. Paul Delsalle. Translated and revised by Margaret Procter. New York: Routledge, 2018. xvii, 245 pp. ISBN 978-1-4094-55240